2014
DOI: 10.1155/2014/878162
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Red Deer Antler Promotes Hair Growth by Regulating the Hair Cycle and Cell Proliferation in Hair Follicles

Abstract: Deer antlers are the only mammalian appendage capable of regeneration. We aimed to investigate the effect of red deer antler extract in regulating hair growth, using a mouse model. The backs of male mice were shaved at eight weeks of age. Crude aqueous extracts of deer antler were prepared at either 4°C or 100°C and injected subcutaneously to two separate groups of mice (n = 9) at 1 mL/day for 10 consecutive days, with water as a vehicle control group. The mice skin quantitative hair growth parameters were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…27 28 It is believed that a variety of important growth factors that drive rapid regeneration of velvet antler may be associated with its growth-promoting activity. 13 In Traditional Chinese Medicine, velvet antler can be regarded as an effective promoter of health, which promotes rapid growth and regeneration by tonic action. 22 However, the detailed underlying mechanism remained less understood.…”
Section: Research Articlementioning
confidence: 99%
“…27 28 It is believed that a variety of important growth factors that drive rapid regeneration of velvet antler may be associated with its growth-promoting activity. 13 In Traditional Chinese Medicine, velvet antler can be regarded as an effective promoter of health, which promotes rapid growth and regeneration by tonic action. 22 However, the detailed underlying mechanism remained less understood.…”
Section: Research Articlementioning
confidence: 99%
“…Pilose antler contains biologically active components including proteins, peptides, amino acids, and a variety of growth factors (such as insulin-like growth factor (IGF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), and nerve growth factor (HGF), which have physiological activities such as promoting wound healing, enhancing immunity, and promoting cell regeneration ( Sui et al, 2014 ). Furthermore, in recent studies, some certain bioactive protein extracts from pilose antler were proven to be delivered through the skin, efficiently fostering hair growth ( Li et al, 2014 ; Tansathien et al, 2021 ), and it has been shown that uridine, a metabolite in pilose antler, has a significant role in hair growth ( Liu et al, 2022 ). However, until now, it’s unclear whether pilose antler could alleviate the AGA disease.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of deer antler extract was believed to strengthen the body, improve immune function, and regulate cardiovascular health and function. In particular, recent studies have reported that the biological effects of deer antler extracts include promotion of hair growth and hematopoietic properties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%